Cynicism in police simulation: a case study of Beat Cop - Popham, James F. (Video games, crime and control, 2024)
Modern video games employ a number of mechanisms that are intended to draw players into the narrative and immerse them in the game, while simultaneously presenting commentary about the police. Our chapter assesses how these mechanisms are presented in a contemporary policing simulator called Beat Cop and examines the immersive representation of policing. Our study employs an ethnographic content analysis approach (Steinmetz, 2018) analyzing the dialog, plot, mechanisms, and activities that make up the majority of Beat Cop’s gameplay. Our findings suggest that the game is highly cynical toward police and their positioning within society, and that this cynicism is not bolstered by any critical or foundational concepts. Rather, Beat Cop reifies populist frames of the police and policing, with particular focus on the “cop” frame suggested by Surrette (2015). We conclude with a critical discussion about the potential sources for this cynicism.